Peran Bimbingan Orang Tua Dalam Upaya Mengurangi Kebiasaan Anak Bermain Game Online - Julywan, Fadhil Arta; Setiana, Wiryo (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
In this modern era, with the rapid advancement of science and technology, activities have become easier. This paper aims to find out how the condition of children in the Citatah Tengah village in playing online games, the forms of online games that are often played by children, the efforts of parental guidance in reducing children's playing online games and how the results of parental guidance in efforts to reduce children's habits playing online games in Citatah Tengah village. The research method uses a descriptive descriptive method which involves data sources from parents who have a habit of children playing online games. The results of the condition study showed that the children in Kp. Citatah is fond of online games, the forms of games that are favored by children are Free Fire and Mobile Legend games. The efforts made by parents include advising, limiting children's games and making rules as a result of guidance efforts made by parents resulting in changes in a positive direction towards children